2004
DOI: 10.1080/13880200490893393
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Neutrophil Pholasin ChemiluminescencebyCleome arabicaLeaf Extract

Abstract: The antioxidative activity of Cleome arabica L. leaf extract was studied toward superoxide anion radical generating systems. The extract at 10 mg=ml has no scavenger effect on superoxide anion radicals generated by the xanthine-xanthine oxidase system, as determined by either the reduction of cytochrome c or pholasin luminescence. Also, this extract, up to 50 mg=ml, did not affect the uric acid production by xanthine oxidase. However, the extract showed a great inhibition activity, in a dose-dependent manner, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Less information is available on botanical extracts that contain a mixture of flavonoids. Cleome arabica is well known in traditional medicine: its botanical extract with high antioxidant capacities (Djeridane et al, 2010;Selloum et al, 2004) could reduce inflammatory conditions both in vivo and in vitro (Bouriche et al, 2003. These effects have been related to the flavonoid content of CALE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less information is available on botanical extracts that contain a mixture of flavonoids. Cleome arabica is well known in traditional medicine: its botanical extract with high antioxidant capacities (Djeridane et al, 2010;Selloum et al, 2004) could reduce inflammatory conditions both in vivo and in vitro (Bouriche et al, 2003. These effects have been related to the flavonoid content of CALE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the polyphenolic extract of C. arabica leaves (CALE) could reduce inflammatory conditions either in vivo by reducing rat paw edema, in vitro by modulating the activity of lipoxygenase and calcium-stimulated generation of the leukotriene B4 and prostaglandin E2 in human neutrophils or also by inhibiting their chemotaxis (Bouriche et al, 2003(Bouriche et al, , 2004. These CALE actions seem to be related to the high content of polyphenolic compounds (Bouriche et al, 2003;Djeridane et al, 2010;Ismail et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation